(untitled) (International Journal of Scientific Trends, 2024)
Knowledge of vocabulary plays an important role in helping students express their thoughts clearly and correctly, understand texts, and achieve academic success during the language learning process. This article describes effective methodologies for developing vocabulary skills in students. The methodology presented will not only help students learn new words, they will also help them use the correct context, as well as express their thoughts richly and clearly.